Predicting persistent back pain causing severe interference with daily activities among community-dwelling older adults: the OPAL cohort study - Williamson, E; Sanchez-Santos, MT; Fairbank, J; Wood, L; Lamb, SE (BioMed Central, 2024)
Background: Many older adults experience disabling back and leg pain. This study aimed to identify factors associated with back pain causing severe interference with daily activities over 2 years. Methods: Participants were 2,109 community-dwelling adults (aged 65–100 years; mean age 74.2 (SD 6.3)) enrolled in a prospective cohort study who reported back pain at baseline and provided back pain data at 2 years follow-up. Baseline data included demographics, socio-economic factors, back pain presentation and age-associated adverse health states (e.g. frailty, falls, walking confidence). At 2 years follow-up, we asked if they were currently experiencing back pain and if so, asked participants to rate how much their back pain interfered with their daily activities on a scale of 0–10. Severe back pain interference was defined by a rating of 7 or more. The association between baseline factors and severe back pain interference at two years was assessed using logistic regression models. Results: At two years, 77% of participants (1,611/2,109) still reported back pain, 25% (544/2,083) also reported leg pain and 14% (227/1,611) reported severe back pain interference with activities. Improvements in symptoms were observed over the two years follow-up in 880/2,109 participants (41.7%), 41.2% (869/2,109) of participants report no change and worsening symptoms was reported by 17.1% (360/2109) of participants. After adjusting for back pain troublesomeness at baseline, factors associated with reporting severe interference were adequacy of income (careful with money [OR 1.91; 95% CI 1.19–3.06]; prefer not to say [OR 2.22; 95% CI 1.11–4.43]), low endorsement of exercise in later life (OR 1.18; 95% CI 1.02–1.37), neurogenic claudication symptoms (OR 1.68 (95% CI 1.15–2.46)], multisite pain (OR 1.13; 95% CI 1.02–1.24) and low walking confidence (OR 1.15; 95% CI 1.08–1.22). Conclusion: After adjusting for baseline pain severity, we identified five factors that were associated with severe pain limitation at two years follow-up among a cohort of community dwelling older people reporting back and leg pain. These included other pain characteristics, walking confidence and attitude to activity in later life. We also identified a socioeconomic factor (perceived adequacy of income). Future research should focus on whether identifying individuals using these risk factors in order to intervene improves back pain outcomes for older people.